PALEOHYDROLOGY OF LAKE BAIKAL IN RELATION TO NEOTECTONICS - Mats V.D.; Fujii S.; Mashiko K.; Granina L.Z.; Osipov E.Yu.; Efimova I.M.; Klimanskii A.V. (My University, 2002)
New data prove that a major rise in the Baikal water level (to 120-150 m) in the Middle Pleistocene may have been caused by tectonic uplift of the western side of the Baikal basin and is marked by medium and high terraces and deltaic sand deposition. As a result of tectonic activity, the outlet of Baikal through the paleo-Manzurka valley to the Lena River was barred 2.0-0.5 Ma ago, and a new outlet appeared through the Il'cha-Irkut valley to the Yenisei system (0.5-0.06 Ma ago). This outflow was substituted by the present Angara outlet that was opened due to collapse of the Listvyanka block about 60 ka ago. Calculations show that a geologically long lake level fall in the past is unlikely, but short low-stand episodes appear probable. The terraces surrounding the lake were produced by the joint effect of hydrology and tectonism. Analysis of the past evolution of the drainage network in the Western Baikal region allowed prediction of its possible future changes.